IoT and QRIS Payment System Integration in Entrepreneurship Lockers to Improve Culinary Business in Schools - Andre Kurniawan Pamudji; Agus Cahyo Nugroho; Bernadinus Harnadi; T Brenda Chandrawati; Erdhi Widyarto Nugroho; FX Hendra Prasetya; Albertus Dwiyoga Widiantoro; Ridwan Sanjaya (Journal of Information System and Informatics, 2023)
The Covid-19 pandemic has disrupted various activities, including the operation of school and campus canteens. In response, innovative solutions are needed to ensure the continuation of the culinary business while keeping all stakeholders safe during the pandemic. This study proposes the development of IoT-integrated entrepreneurial lockers that enable cashless payments through QRIS. These lockers can be used to revive the culinary business in school and campus canteens that had to close due to the pandemic. The results of the study show that the use of these lockers can reduce physical contact during transactions, thus minimizing the risk of virus transmission. Overall, this research offers a practical solution for sustaining the canteen business in the face of the pandemic.